An application of double Laplace transform and double Sumudu transform - Kilicman, Adem; Gadain, Hassan Eltayeb (SP MAIK Nauka/Interperiodica, 2009)
In this paper, we produce some properties and relationship between double Laplace and double Sumudu transforms. Further, we use the double Sumudu transform to solve wave equation in one dimension having singularity at initial conditions.